Environmental management activities of an infrastructure development project: the case of Beris Dam, Malaysia - Nik Norulaini Nik Ab. Rahman; Asyirah Abdul Rahim; Fera Fizani Ahmad Fizri (Environmental Management Society, Malaysia, 2006)
Development projects need to integrate environmental dimensions into project management functions to ensure successful implementation of environmental management and control practices throughout the development process. The management functions include the scope of work for environmental control, the quality of work or performance to be delivered, the scheduling for environmental works, and the most important one is the budget for environmental control. The aim of this paper is to examine and discuss about the environmental dimensions of Beris Dam during its construction and development process. The environmental dimension criteria and elements of the project were examined by means of reviewing environmental control documents used in the project’s construction and development, and site visits. The review reveals that in general the Beris Dam EIA and EMP reports scored between ‘unsatisfactory’ to ‘good’ for the criteria and elements of good environmental practice. These findings indicate the need to increase both effort and implementation of environmental dimensions in project management to help improve the success of implementing environmental management activities in the construction and development of a project